2023
DOI: 10.1039/d3gc01898a
|View full text |Cite
|
Sign up to set email alerts
|

Designing an enzyme assembly line for green cascade processes using bio-orthogonal chemistry

Abstract: Two non-canonical amino acids (ncAAs) with bio-orthogonal reactive groups, namely, p-azido-L-phenylalanine (p-AzF) and p-propargyloxy-L-phenylalanine (p-PaF), were genetically inserted into an aldo-keto reductase (AKR) and an alcohol dehydrogenase (ADH), respectively, at...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…Based on our previous studies, the mutant sites for AKR were identified as 130S, 162Q, 189Q, and 232W, and these sites were 104A, 125I, 155Y, 199P, and 204A for ADH. [18,23] The selection principles for mutation sites are as follows. 1) far from the active center; 2) less impact on the protein structure, considering similar group size or electronegativity; 3) located on the surface of a protein.…”
Section: Construction Of Fused Enzymes and Their Mutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our previous studies, the mutant sites for AKR were identified as 130S, 162Q, 189Q, and 232W, and these sites were 104A, 125I, 155Y, 199P, and 204A for ADH. [18,23] The selection principles for mutation sites are as follows. 1) far from the active center; 2) less impact on the protein structure, considering similar group size or electronegativity; 3) located on the surface of a protein.…”
Section: Construction Of Fused Enzymes and Their Mutantsmentioning
confidence: 99%
“…[17] In our previous work, we constructed a nano-reactor with a multienzyme assembly to synthesize chiral pharmaceutical intermediates by incorporating non-canonical amino acids (ncAAs) into enzymes. [18] In this work, we proposed a dualenzyme ordered coating strategy that combines the advantages of carrier and carrier-free immobilization. A dualenzyme cascade system was developed to synthesize (S)-1-(2-chlorophenyl)ethanol from o-chloroacetophenone by regenerating the cofactor NADPH in situ.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, crosslinking is the most promising technique that allows for the incorporation of enzymes and redox molecules onto the support platform [94]. In order to create the enzyme cascade system, the crosslinking technique is employed to co-immobilize different enzymes on the support surface with close proximity, thus allowing for its catalytic efficiency and reusability [95]. In addition, in some cases, the crosslinking technique can also control spatial distance and substrate channeling to attain catalytic efficiency [96].…”
Section: Crosslinked Supportmentioning
confidence: 99%